(3GdEYdGe HeKdK GdcdGes - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf GdeNJGQ ZGdi Hf GdeUWai Hf CMeO QRhb s)
(3ChdgG (B:s
(3bGd GdabjQ Edi QMeI QHg , GdeSJhgH eZaQI PfHg GJHGY CMeO Gdedc GdhgGH , hUdGJg Ydi GdQVi GdChGH eMeO GdChGH eMeO hBdg hGdCfLGH , Hg GHJgGL GdfWa ai GdcJGH HGH eG KdK daXg hGJMO eYfGg s
(3BNQgG (B:s
(3HGH eG Chdg jGA ef GdeKdK GdeNJda GdeYGfi (B: (3VQH GdjSGQ , hJbGSe GdLRQ , hGdVQH HGdbOGM ef (B" (3jSQ (B" (3agPG BNQ GdcJGH , aCMeO Gddg HdG GfJgGA , eSJJHY GdUdGI hGdKfGA , Ydi GdfHi NjQ GdCfHjGA s
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeIs
(3YfGhjfgG HGdMeQI s
(3hHgG BKGQ QWhHI TOjOI hCQVg hMhGagG eJBcdI HTOI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GddZIs